2010
DOI: 10.1007/s11079-010-9166-0
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Exchange Rates on Investment in Mexican Manufacturing Industry

Abstract: Exchange rate volatility, Investment, External exposure, Market structure, E22,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
(21 reference statements)
1
7
1
Order By: Relevance
“…According to Caglayan and Torres (2011), the depreciation of the Mexican currency resulted in more FDI inflow whilst exchange rate volatility negatively impacted on FDI especially in the export oriented sectors of the Mexican economy. Furthermore, Caglayan and Torres (2011) showed that the impact of exchange rate volatility on FDI to a larger extent was much stronger in the non-durable goods sectors of the Mexican economy during the period 1994 to 2003.…”
Section: Review Of Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…According to Caglayan and Torres (2011), the depreciation of the Mexican currency resulted in more FDI inflow whilst exchange rate volatility negatively impacted on FDI especially in the export oriented sectors of the Mexican economy. Furthermore, Caglayan and Torres (2011) showed that the impact of exchange rate volatility on FDI to a larger extent was much stronger in the non-durable goods sectors of the Mexican economy during the period 1994 to 2003.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Furthermore, Caglayan and Torres (2011) showed that the impact of exchange rate volatility on FDI to a larger extent was much stronger in the non-durable goods sectors of the Mexican economy during the period 1994 to 2003. Greenaway et al (2012) on the other hand discovered that multinational enterprises whose origin was outside the European Union (EU) were the least affected by exchange rate volatility whilst the multinational enterprises from the EU region were found to be more susceptible to exchange rates changes.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Second, the findings conclude that the impact of exchange rate depreciation on the total investment is positive, when exchange rate uncertainty is at low levels. Furthermore, Caglayan and Torres [8] investigate the association between exchange rate and exchange rate volatility and capital investment of Mexican manufacturing firms. They conduct a panel data analysis on the firms for the period of 1994-2003.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies show a negative relationship (Ojeyinka and Adegboye, 2017; Falaye, 2019;Vo and Zhang, 2019;Irene et al, 2020). Similarly, Caglayan and Torres (2011) investigate the effects of the exchange rate in the Mexican manufacturing sector from 1994 to 2003 by using fixed capital investment as an intermediate channel. They found that currency depreciation positively affects fixed investment through the export channel but a negative effect through the import channel.…”
Section: Gross Fixed Capital Formation and Manufacturingmentioning
confidence: 99%